2017
DOI: 10.1080/03639045.2017.1386208
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent crystals of gliclazide and tromethamine: preparation, physico-chemical, and pharmaceutical characterization

Abstract: The new system shows an improved pharmaceutical behavior and could be formulated in a dosage form to obtain a rapid and complete release of the drug available for absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…4). The endothermic peak at 170.5 °C, is the melting point of TM, whereas at 137.1 °C is a temperature of a solid-state transition [24]. The multicomponent crystal shows a single endothermic peak (110 °C) which is different from the two constituent components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). The endothermic peak at 170.5 °C, is the melting point of TM, whereas at 137.1 °C is a temperature of a solid-state transition [24]. The multicomponent crystal shows a single endothermic peak (110 °C) which is different from the two constituent components.…”
Section: Resultsmentioning
confidence: 99%
“…TM is a GRAS (generally recognized as safe) excipient according to FDA (the US Food and Drug Administration) and is widely used as an alkalizer and biological buffer. Moreover, TM is also used as a salt co-former for some weak acid drugs to improve the physicochemical properties [23,24]. To our knowledge,…”
Section: Introductionmentioning
confidence: 99%
“…The infrared absorption spectra of drug, coformer, and the cocrystal were obtained using FTIR spectrophotometer (IR Synthons in pharmaceutical cocrystals [16,17] a b…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…Various approaches to improve the dissolution behaviour of GLZ have been pursued including micronization (Varshosaz et al, 2008), encapsulation into nanoparticles (Devarajan and Sonavane, 2007;Naik et al, 2013), dispersion into polymers (Hong et al, 1998;Biswal et al, 2008Biswal et al, , 2009aJondhale et al, 2012;Lu et al, 2017), salt formation (El-Sabawi and Hamdan, 2014;Putra et al, 2016a,b;Samie et al, 2017) and complexation with cyclodextrins (Winters et al, 1997;Özkan et al, 2000;Aggarwal et al, 2002). More recently, a limited number of studies on GLZ cocrystals were also reported (Chadha et al, 2016(Chadha et al, , 2017Samie et al, 2017;Bruni et al, 2018). Chadha and coworkers used the GRAS (Generally Recognized as Safe) coformers succinic acid, malic acid, sebatic acid and -hydroxyacetic acid to obtain multicomponent crystals of GLZ with enhanced dissolution properties (Chadha et al, 2016(Chadha et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The cocrystallization of GLZ with catechol and resorcinol was studied by Desiraju and coworkers (Samie et al, 2017). Bruni et al reported a multicomponent crystal of GLZ and the excipient tromethamine (Bruni et al, 2018). Uekusa and coworkers cocrystallized GLZ with the antidiabetic drug metformin and obtained a salt with a significantly improved solubility and dissolution rate (Putra et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%